Analysis of hallucinations and fear complex cause for psychological abnormalities of the protagonist Brutus Jones In Eugene O’Neill’s The Emperor Jones - Nallathambi, M.; Gnanasekaran, T. (International Journal of Psychosocial Rehabilitation, 2019)
In order to explore the fundamental themes of human life itself—the endless conflicts of good and evil, of light and darkness, of civilization and savagery—O’Neill experimented with expressionistic techniques in some of his early plays. In The Emperor Jones, published in 1921, O’Neill makes special use of symbolic scenes and sound effects to portray certain psychological states of mind, hallucinations, and the emotional intensity of his protagonist, Brutus Jones. This study reveals the psychological abnormalities of the protagonist, Brutus Jones The Emperor Jones is arranged in eight scenes, dramatizing the psychological journey of an island in the West Indies to a man acknowledging his guilt, attempting to do away with the evil in himself, and finally accepting his humanity. Central to the process of this journey are Jones’ feelings of isolation and his quest for belonging. The present study explains the scene-wise summary of the psychological abnormalities, struggles, and tragic end of the hero Brutus Jones.